2020
DOI: 10.4314/afrrev.v13i3.15
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to capital budget implementation in Nigeria

Abstract: This study empirically assessed the constraints to capital budget implementation in Nigeria. The methodology employed was both descriptive and analytical. Primary survey instrument was developed and distributed to 200 respondents in 20 federal ministries, departments and agencies within two contiguous states in the South-south geopolitical zone in the country. The ensuing data were analysed using multiple regression as well as correlation analyses. Results indicated, inter alia, that delay in budget presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Though listed among the African Countries with high annual budget percentage allocation, Nigeria's allocation to education is below the 12% allocation of Burundi and Mozambique (After South Africa, 2020). Nigeria's situation is compounded by high corruption in budget implementation (Effiom and Edet, 2019;Nelson and Yebimodei, 2018).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Though listed among the African Countries with high annual budget percentage allocation, Nigeria's allocation to education is below the 12% allocation of Burundi and Mozambique (After South Africa, 2020). Nigeria's situation is compounded by high corruption in budget implementation (Effiom and Edet, 2019;Nelson and Yebimodei, 2018).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The study's findings suggested that all factors had no significant influence on economic growth in the short run, and that they continue to have no significant influence on economic growth in the long run. Effiom & Edet (2019) examined the limits on Nigeria's capital budget execution. Primary data sources were a survey instrument produced and delivered to 200 respondents in 20 federal ministries, departments, and organizations located in two adjacent states in the country's south-south geopolitical zone.…”
Section: Objectives Of the Studymentioning
confidence: 99%
“…All of the variables tested had no affect on growth in the short run, but in the long run, they had no affect on growth. Nigeria's capital budget execution has been characterized by consistent difficulties over the last three years, according to researchers from Effiom & Edet (2019). This data was acquired from primary sources, which included mailing out a survey to 200 federal employees in two southern states in the South-South geopolitical zone.…”
Section: Empirical Reviewmentioning
confidence: 99%